Anxiety, depression and coping: CDI, MASC and CRI-Y for screening purposes in schools - Matos, M. G.; Tomé, G.; Borges, A. I.; Manso, D.; Simões, C.; Ferreira, A. (The Spanish Journal of Psychology, 2012)
This study used depression (CDI – Kovacs, 1981), anxiety (MASC – March, 1997) and coping strategy (CRI-Y – Moos, 1993) scales and studied the fitness and discriminant validity of reduced versions. The sample consisted of 916 Portuguese pupils, 54.3% feminine, aged 10 to 21 years old. The participants were selected from a set of public schools nation-wide. Two classes were chosen from the 5th to the 12th grades. A set of principal component analyses was carried out in a randomly chosen sample (n = 394) and all the three reduced measures were found to be strongly correlated with the previous. Confirmatory factor analyses (CFA) using the other part of the sample (n = 522) revealed adjustment indexes suggesting a good fit for both the whole model and gender and age groups separately. All scales revealed a good internal consistency. Globally, girls were more anxious and developed more coping strategies than boys. Older students tended to be less depressed, while younger adolescents present higher scores in depression and anxiety and less coping strategies. Reduced scales are sensitive to gender and age differences and can be used in school settings in order to establish a baseline and roadmaps for both universal and selective mental health school based programs.